Drug-Eluting Bead Bronchial Arterial Chemoembolization With and Without Microwave Ablation for the Treatment of Advanced and Standard Treatment-Refractory/Ineligible Non-Small Cell Lung Cancer: A Comparative Study - Xu, Sheng; Bie, Zhi-Xin; Li, Yuan-Ming; Li, Bin; Kong, Fan-Lei; Peng, Jin-Zhao; Li, Xiao-Guang (Frontiers in Oncology, 2022)
Purpose: To compare the outcomes of drug-eluting beads bronchial arterial chemoembolization (DEB-BACE) with and without microwave ablation (MWA) for the treatment of advanced and standard treatments-refractory/ineligible non-small cell lung cancer (ASTRI-NSCLC). Materials and Methods: A total of 77 ASTRI-NSCLC patients who received DEB-BACE combined with MWA (group A; n=28) or DEB-BACE alone (group B; n=49) were included. Clinical outcomes were compared between groups A and B. Kaplan–Meier methods were used to compare the median progression-free survival (PFS) or overall survival (OS) between the two groups. Univariate and multivariate Cox proportional hazards analyses were used to investigate the predictors of OS for ASTRI-NSCLC treated with DEB-BACE. Results: No severe adverse event was found in both of the groups. Pneumothorax was the predominant MWA-related complication in group A, with an incidence rate of 32.1% (9/28). Meanwhile, no significant difference was found in DEB-BACE related complications between groups A and B. The overall disease control rate (DCR) was 61.0% (47/77), with a significantly higher DCR in group A (85.7% vs 46.9%, P=0.002). The median PFS in groups A and B were 7.0 and 4.0 months, respectively, with a significant difference (P=0.037). The median OS in groups A and B were both 8.0 months, respectively, with no significant difference (P=0.318). The six-month PFS and OS rates in groups A and B were 75.0% and 78.6%, 22.4% and 59.2%, respectively, while the 12-month PFS and OS rates in groups A and B were 17.9% and 28.6%, 14.3% and 22.4%, respectively. Of these, a significantly higher six-month PFS rate was found in group A (75.0% vs 22.4%; P<0.001). The cycles of DEB-BACE/bronchial artery infusion chemotherapy (hazard ratio [HR]:0.363; 95% confidence interval [CI]: 0.202-0.655; P=0.001) and postoperative immunotherapy (HR:0.219; 95% CI: 0.085-0.561; P=0.002) were identified as the predictors of OS in ASTRI-NSCLC treated with DEB-BACE. Conclusion: MWA sequentially combined with DEB-BACE was superior to DEB-BACE alone in the local control for ASTRI-NSCLC. Although the combination therapy reveals a trend of prolonging the OS, the long-term prognosis is warranted to be investigated with a longer follow-up.